Efektifitas Pijat Bayi Terhadap Penambahan Berat Badan Bayi Di Klinik Kusuma Husada Bayat - Piscolia Dynamurti Wintoro; Astri Wahyuningsih (Stikes Muhammadiyah Klaten, 2022)
Baby massage is one of the recommended stimulations to stimulate the development of brain cell function. Baby massage has a hungry effect on babies due to an increase in vagus nerve muscle tone to facilitate the release of food absorption hormones and increase levels of gastrin and insulin enzymes so that babies who are massaged experience weight gain more rapidly. The purpose of this study was to determine the effectiveness of infant massage on infant weight gain at the Kusuma Husada Bayat Clinic. The design of this research was descriptive correlation with a retrospective approach. The research sample was all babies who did baby massage from February to March 2021 at the Kusuma Husada Bayat Clinic. A total of 32 babies. The sampling technique used total sampling. The instrument used was an observation sheet. Data analysis using chi square test. The results of the study of babies who did routine baby massage had a weight increase of 21 with a percentage of 65.6% while babies who did not routinely do baby massage did not increase their weight by 9 babies with a percentage of 28.1% and the results of bivariate analysis obtained p value 0.000 ( p < 0.05). The conclusion of this study is that Baby Massages effective in increasing infant weight at the Kusuma Husada Bayat Clinic, Klaten. It is recommended that mothers massage their babies more regularly because of the many benefits and good effects for the health and growth of babies